A. Sánchez-Ostiz, J. B. Torres Guerra y R. Martínez, De Grecia a Roma y de Roma a Grecia. Un camino de ida y vuelta, Pamplona, Ediciones de la Universidad de Navarra, 2007, 431 pp. (Minerva, 2019)
Review: A. Sánchez-Ostiz, J. B. Torres Guerra y R. Martínez, De Grecia a Roma y de Roma a Grecia. Un camino de ida y vuelta, Pamplona, Ediciones de la Universidad de Navarra, 2007, 431 pp.